MODELING AND OPTIMIZATION OF PARALLEL INFORMATION SEARCHING IN FILES - Lisovets, Volodymyr; Tsehelyk, Hryhoriy (International Journal of Computing, 2014)
In this article the m-parallel method of sequential field searching and two variants of m-parallel block field searching method are offered. These methods are oriented to be used in multiprocessing system for information searching in files of database. We research the effectiveness of these methods for different probability distribution law of field access. The mathematical expectation of number of parallel comparisons necessary for field searching in files is taken as a criterion of effectiveness. The effectiveness of the methods is compared and analyzed. The best of offered methods is founded for every considered probability distribution. Optimal strategies of field searching in sequenced files stored in external memory of multiprocessing system are made. In this case the mathematical expectation of total time needed for field searching in files is taken as a criterion of effectiveness.